Azerbaijan Demographic Change : Implications for Social Policy and Poverty - World Bank (World Bank, 2012)
This note provides an overview of demographic changes in Azerbaijan and their policy implications. Azerbaijan's population is younger than the populations of most countries in the region. It is estimated that the population in Azerbaijan will increase from about 7.2 million in 1990 to 10.6 million by 2050. Nevertheless, Azerbaijan is beginning to experience the aging of its population, after having undergone a dramatic decline in fertility from about 5.5 children per woman in the 1950s, to just over two children per woman at present. This trend, combined with increasing life expectancy, underlies the growing rise in the percentage of elderly persons, and the eventual slowdown in the growth of the working-age population. This note provides an overview of key demographic changes unfolding in Azerbaijan, highlights their linkages with social spending, and draws policy implications for labor force participation, productivity, and ultimately for Azerbaijan's development and poverty reduction trajectory. The major driver of Azerbaijan's demographic shift is an aging population. The country has already undergone a dramatic decline in its fertility rate, which fell from about 5.5 children per woman in the 1950s to the present level of just over 2 children per woman. This trend, combined with increasing life expectancy, underlies the evolution in the age structure of Azerbaijan's population. The two main demographic changes evident from these trends are a rise in the percentage of elderly persons, and a slowdown and eventual shrinkage of the working-age population.